Magnetoresistance of multi‐walled carbon nanotubes modified with iron. Issue 2 (13th March 2013) - Ovsienko, I. V.; Matzui, L.Y.; Yatsenko, I. V.; Khrapatiy, S. V.; Prylutskyy, Y. I.; Ritter, U.; Scharff, P.; Le Normand, F.
Abstract The dependence of the magnetoresistance of iron‐doped multi‐walled carbon nanotubes (Fe‐MWCNTs) on the carbon nanotubes arrangement, the temperature, the relative orientation of the magnetic field, and the current was investigated. The findings show that the magnetoresistance of partially‐oriented Fe‐MWCNTs is due to a combination of two mechanisms: (1) the giant magnetoresistance (GMR) that takes place in layered or cluster systems consisting of magnetic and nonmagnetic materials, and (2) the anisotropic magnetoresistance which is characteristic of ferromagnetic metals. For array‐oriented Fe‐MWCNTs the dominant mechanism of magnetoresistance depends on the relative orientation of the magnetic field and current through the sample, namely it depends on the localization mechanism at the mutually perpendicular orientation of the magnetic field and current and the GMR effect in mutual parallel orientation of the magnetic field and current.